Higher incidence of low birth weight infants among malay women with periodontitis in Kota Bharu, Kelantan - Norkhafizah, S,; Norsa'adah, B.,; Zainuddin, S.L.A.,; Sosroseno, W.,; N. Hazlina, N.H., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
The causes of low birth weight (LBW) are complex and multifactorial. Current epidemiological and microbiological studies have suggested that maternal periodontal infection may increase the risk of delivering LBW infants. The objective ofthis prospective cohort study was to determine the incidence of LBW infants among pregnant women with periodontitis. Malay pregnant women were recruited from two selected Klinik Kesihatan Ibu dun Anak (KKIA) in the district of Kota Bharu. Of 472 women studied, 232 who had periodontitis were classfied as being exposed, while the rest who did not have periodontitis were in the non-exposed group. The incidence of LBW was 14.2% (95% CI: 9.7-18.8) in women with periodontitis, and 3.3% (95% CI: 1.1-5.6) in women without periodontitis. Pregnant women with periodontitis are at higher risk of delivering LBW infants (p<0.001). This knowledge should increase physician and patient awareness to the relevance of oral infections. Ultimately, it should help to establish the groundwork for closer communication between the medical and dental colleagues to improve the quality of antenatal care towards achieving our vision and goals for health.